2017
DOI: 10.1007/s12687-017-0317-5
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of diverse populations in genomic research and health services: Genomix workshop report

Abstract: Clinical genetic services and genomic research are rapidly developing but, historically, those with the greatest need are the least to benefit from these advances. This encompasses low-income communities, including those from ethnic minority and indigenous backgrounds. The "Genomix" workshop at the European Society of Human Genetics (ESHG) 2016 conference offered the opportunity to consider possible solutions for these disparities from the experiences of researchers and genetic healthcare practitioners working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 60 publications
(57 reference statements)
0
25
0
Order By: Relevance
“…A study exploring the views of people from UK Black African and Black Caribbean communities showed a lack of organizational commitment, economic support, policies, practice, strategic vision, and leadership in engaging these participants in the 100,000 genomes project (Skyers, 2018). Literature focusing on ethnic disparities in genomic research has shown the need for a global approach, strategic vision, funding, development of skilled workforce, and community engagement programs promoting equitable access to genomics (Bentley et al, 2017; Mathew et al, 2017), but little progress has been made yet.…”
Section: Introductionmentioning
confidence: 99%
“…A study exploring the views of people from UK Black African and Black Caribbean communities showed a lack of organizational commitment, economic support, policies, practice, strategic vision, and leadership in engaging these participants in the 100,000 genomes project (Skyers, 2018). Literature focusing on ethnic disparities in genomic research has shown the need for a global approach, strategic vision, funding, development of skilled workforce, and community engagement programs promoting equitable access to genomics (Bentley et al, 2017; Mathew et al, 2017), but little progress has been made yet.…”
Section: Introductionmentioning
confidence: 99%
“…There are also populations that will need further consideration and engagement; patient groups, Aboriginal and Torres Strait Islanders communities, and cultural and linguistically diverse communities. Based on other work, these groups are likely to have different perspectives and expectations on sharing of clinical genomic data and biological samples for research purposes (11,17,34,35).…”
Section: Policy Directions and Future Workmentioning
confidence: 99%
“…Participants were provided with a written information sheet prior to starting the online questionnaire. (17) 149 (12) 126 (10) 156 (13) Police using genomic databases with my details to investigate crimes 474 (38) 141 (11) 137 (11) 142 (12) 339 (27) Receiving information about my future health that has no treatment option 431 (35) 194 (16) 191 (15) 155 (13) 262 (21) My family finding out about my health results 242 (20) 140 (11) 140 (11) 142 (12)…”
Section: Authors Contributionmentioning
confidence: 99%